Pernikahan Dini Meningkatkan Risiko Kejadian Kanker Serviks - Kurniasari Pratiwi; Yuni Fitriana (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2021)
Background: The incidence and mortality from cervical cancer (cervical cancer) in the world second only to breast cancer. Meanwhile, in developing countries still ranks as the top cause of cancer deaths in the reproductive age. Cancer of the cervix is still a threat for women so it is called the